GAMBARAN FAKTOR PERILAKU DAN FAKTOR LINGKUNGAN DI DAERAH ENDEMIS MALARIA (Studi di Daerah Endemis Rendah dan Daerah Endemis Tinggi Kecamatan Bagelen Kabupaten Purworejo Tahun 2015) - Siti Maryatul Keptiyah; Martini Martini; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Purworejo is a Regency which endemic malaria in Central Java. The highest Malaria cases in Central Java in 2013, is located in the County. This research aims to provide an overview of behavior factors and environmental factors in areas of endemic malaria. This research is descriptive research type through cross sectional approach. Samples taken with a stratified random sampling technique. Sample research totalling 120 respondents. The results showed that the majority of respondents knowledgeable good (65%), the attitude of respondents towards the good as much as 70,7%, respondents who use the mosquito nets and insect repellent is the same that is as much as 48,3%, of the community which have activities outside of the home during the night that do not risk 73,3%, most people do not use a wire gauze on vent (89,2%), a mosquito breeding places closer to home 76,7%, the majority of the community have a distance of houses close to the enclosure of livestock (69,2%), as many as 70% of the larva density in this area belongs not to solid. The community should further enhance malaria prevention efforts so that the number of cases of malaria can be decreased up to elimination.